The Internet of Everything Advances, Challenges and Applications - Dey, Nilanjan; Shinde, Gitanjali; Mahalle, Parikshit; Olesen, Henning (De Gruyter, 2019)
In the era before IoT, the world wide web, internet, web 2.0 and social media made people's lives comfortable by providing web services and enabling access personal data irrespective of their location. Further, to save time and improve efficiency, there is a need for machine to machine communication, automation, smart computing and ubiquitous access to personal devices. This need gave birth to the phenomenon of Internet of Things (IoT) and further to the concept of Internet of Everything (IoE).